2007
DOI: 10.1002/chem.200601429
|View full text |Cite
|
Sign up to set email alerts
|

A Fluorous, Pummerer Cyclative‐Capture Strategy for the Synthesis of N‐Heterocycles

Abstract: A fluorous, cyclative-capture strategy based on a new Pummerer cyclization process allows rapid access to tagged, heterocyclic frameworks. Convenient modification of the fluorous, heterocyclic scaffolds by using a variety of approaches including Pd-catalyzed cross-couplings is possible. Traceless, reductive cleavage of the fluorous-phase tag or oxidative cleavage and further elaboration, completes a strategy for the high-throughput, fluorous-phase synthesis of a diverse range of N-heterocycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 56 publications
2
18
0
4
Order By: Relevance
“…The acidity of the 1,3‐dicarbonyl methylene protons in 13 c enabled conversion to α,α‐dimethylketone 47 in a one‐pot geminal dimethylation . Sonogashira coupling of the aryl bromide moiety in 47 with phenyl acetylene then afforded aryl alkyne 48 in 65 % yield . From the parent aryl bromide 13 c , several boronic acids were also coupled under standard Suzuki–Miyaura conditions to provide cross‐coupling products 49 – 51 in good yields.…”
Section: Resultsmentioning
confidence: 99%
“…The acidity of the 1,3‐dicarbonyl methylene protons in 13 c enabled conversion to α,α‐dimethylketone 47 in a one‐pot geminal dimethylation . Sonogashira coupling of the aryl bromide moiety in 47 with phenyl acetylene then afforded aryl alkyne 48 in 65 % yield . From the parent aryl bromide 13 c , several boronic acids were also coupled under standard Suzuki–Miyaura conditions to provide cross‐coupling products 49 – 51 in good yields.…”
Section: Resultsmentioning
confidence: 99%
“…The Procter group has utilized a connective approach to thionium ions from aldehyde and thiol starting materials that involves the in situ formation and activation of hemithioacetal intermediates 56 (Scheme ) 27. 28 The connective Pummerer reaction has a number of attractive features: it uses readily available starting materials, does not require the synthesis of sulfides and sulfoxides, and is useful for convergent synthesis as the structural features of the aldehyde, thiol, and nucleophile are incorporated into the product.…”
Section: Pummerer Reactions Using An Alternative Methods Of Thioniumentioning
confidence: 99%
“…[240] Procter showed that microwave heating promoted the amination of oxindole aryl bromides bearing a fluorous tag which could later undergo traceless removal (Scheme 68). [241] Microwave irradiation was used by workers at GlaxoSmithKline in a key coupling step in the synthesis of analogues of CRF 1 receptor antagonists for the treatment of stress-related disorders (Scheme 69). [242] It was found that by using microwave irradiation and MePhos as ligand reaction times were minimized and yields maximized.…”
Section: Development Of Reaction Conditionsmentioning
confidence: 99%